SEXUALLY DIMORPHIC RADULAR MORPHOLOGY IN Columbella mercatoria ( MOLLUSCA: GASTROPODA: COLUMBELLIDAE) - Bandeira, Ênio Victor Paiva; Rabay, Soraya Guimarães; Cascon, Helena Matthews (Arquivos de Ciências do Mar, 2014)
Radular morphology in (Linnaeus, 1758) was investigated for the occurrence of sexual dimorphism. Thirty adult specimens of C. mercatoria (15 males and 15 females) were collected in the intertidal zone of the Farol do Trapiá Beach (2°51’S - 40°51’W) Camocim and Banco dos Cajuais Beach (4°40’S - 37°20’W) Icapuí, State of Ceará, Northeast Brazil, from May to June of 2012. The animals were fixed and had the shell length measured. The radula of six males and six females was separated and measured, and sixty lateral and rachidian teeth of both females and males had six and two dimensions measured, respectively. For males, the average length of radula ribbon was 7.24 ± 0.72 mm and that of females was in average 7.92 ± 1.02 mm. The difference was statistically significant (p= 0.047). The test revealed a positive significant correlation between shell length and the lengths of radula ribbon of males (R 2 = 0.767) and females (R 2 = 0.508)